Systemic Modeling of Agent Coaction: A Catalog of Decentralized Coordinating Processes - Sudeikat, Jan (Electronic Communications of the EASST, 2010)
Taking inspiration from natural self-organizing systems is a successfulstrategy to solve computational problems in distributed systems. Faced with a particularproblem, application designers have to identify an appropriate dynamical behaviorand decide how to induce similar behavioral modes. In order to consolidatethese ad-hoc activities to a systematic dynamical design method, we discuss and exemplifya behavioral modeling approach that describes the macroscopic behavior ofagent-based software systems. This formalism is used to catalog the dynamic behaviorof prominent examples of natural self-organizing systems. These here presentedmodels represent generic, reusable templates for decentralized system adaptationsthat serve as analysis templates for application designs. A tailored programmingmodel allows to supplement these templates in agent-based software applicationswith minimal intervention in the agent models.